A Review of Literature on Parenting Styles, Parental Competence and Emotional Intelligence among College Students (Medico Legal Update, 2021)
Parenting styles and competence predict many aspects of the children’s well-being. Studies indicate thatparents present the first learning environment for their children before joining schools, and that the impactsthey have to their children may influence their children up to college level. Although many studies have beenconducted on the impacts of parenting style and parental competence on emotional intelligence, majorityof these are mainly in the context of Western or Asian countries and little, or none in the context Nigeria,particularly, in urban area of Anambra State. Therefore, the general objective of the study is to conceptualizethe relationships of parenting style and parental competence on emotional intelligence of college students inurban area of Anambra state, Nigeria.